Revisiting Photovoice: Perceptions of Dementia Among Researchers With Intellectual Disability. (June 2020) - Watchman, Karen; Mattheys, Kate; Doyle, Andrew; Boustead, Louise; Rincones, Orlando
There is limited global evidence exploring perceptions of dementia among people with intellectual disabilities. This article presents findings from the first known study where an inclusive research team, including members with intellectual disability, used photovoice methodology to visually represent views of people with intellectual disabilities and dementia. Drawing on Freire's empowerment pedagogy, the study aims were consistent with global photovoice aims: enabling people to visually record critical dialogue about dementia through photography and social change. We investigated the benefits and challenges of photovoice methodology with this population and sought to identify perspectives of dementia from people with intellectual disabilities. Data collected identified issues such as peers "disappearing" and the importance of maintaining friendship as dementia progressed. Although reaching policymakers is a key aim of photovoice, this may not always be achievable, suggesting that revisiting Freire's original methodological aims may lead to improved outcomes in co-produced research with marginalized groups.